The effects of education based on the Roy adaptation model on medication adherence and psychosocial adjustment in hypertensive patients - Demirel, Cihat; Kilic, Serap Parlar (Elsevier Science Inc, 2024)
Background and Aim: Patient education utilizing nursing theory can enhance patient adherence to treatment and potentially decrease mortality rates. The objective of this investigation was to assess the impact of Roy's adaptation Model -focused education on medication adherence and psychosocial compliance in hypertensive patients. Methods: This study was conducted in N = 60 hypertensive patients ( n = 30 control group and n = 30 experimental group) based on a randomized controlled trial design. In the pre-test phase of the study, data was collected using the Patient Information Form, the medication adherence rating scale (MARS), and the psychosocial adjustment to illness scale -self -report (PAIS-SR). After the pre-test phase, the experimental group received hypertension education and the Hypertension Education Booklet for a duration of four weeks. No education was provided to the control group patients; only routine follow-ups were conducted. In the post-test phase (after four weeks), both groups were reassessed using MARS and PAIS-SR. After completing the study, the control group patients who volunteered to participate in the education were provided with hypertension education and the Hypertension Education Booklet for a duration of four weeks ( n = 4). Results: The post-test measurements of patients in the experimental group (after 4 weeks of education) revealed an increase in the mean MARS scores (6.50 +/- 0.86) and a significant decrease in the total and subscale mean scores of PAIS-SR (24.12 +/- 7.08) ( p < 0.05). No changes were observed in the control group patients. Conclusion: The results of the study revealed that the education based on the Roy's Adaptation Model increased hypertensive individuals' medication adherence and physiological, psychological, and social adjustment to the disease. Relevance to clinical practice: The education based on the Roy's Adaptation Model seems to be effective in increasing patients' adherence to treatment and adjustment to the disease. This model can be used in various diseases and societies, since it increases adjustment to the disease and the effectiveness of treatment. (c) 2024 Society for Vascular Nursing, Inc. Published by Elsevier Inc. All rights reserved.